IFN-γ VERSUS IL-10 IN SITU EXPRESSION IN RECURRENT SPONTANEOUS ABORTION (Iraqi Journal of Medical Sciences, 2009)
Background: The possible immunological bases of recurrent spontaneous abortion (RSA) are still largely unknown, aberrant type 1 cytokine production; interferon-γ (IFNγ), and a defective type 2 cytokine; Interleukin-10 (IL-10) has been suggested to be related to the incidence of unexplained RSA.Objective: To study the relation between the in situ expression of IFNγ and IL-10 in women with recurrent spontaneous abortion.Materials and Methods: The study included three groups of women; Group A: patients had recurrent abortion (n=24), Group B: patients had spontaneous abortion for the first time (n=10), Group C: women with elective pregnancy termination (n=6). Curate samples obtained from these women were subjected for in situ hybridization technique to detect and determine the in situ expression of IFN-γ and IL-10.Results: The in situ expression of IFN-γ was significantly higher in women with RSA as compared with normal pregnant and first abortion groups (p=0.000 and 0.002 respectively), while IL-10 expression was significantly lower in women with RSA as compared with first abortion group (p=0.005), and the ratio of IFN-γ/IL-10 was 1.97 in women with recurrent abortion, while that of normal pregnant and first abortion groups were 0.67 and 0.73 respectively.Conclusion: The data of this study strengthened the possibility that type-1 immune response may have the upper hand in the pathology of RSA in association with reduction in the type-2 immune response.Key words: RSA, IFN-γ, IL-10